Evaluation of different procedure involved in the Transcranial Direct Current Stimulation (tDCS) technique experimental application - Spezia Adachi, Lauren Naomi; de Oliveira, Carla; Vercelino, Rafael; de Macedo, Isabel Cristina; Laste, Gabriela; Quevedo, Alexandre Silva; Scarabelot, Vanessa Leal; Caumo, Wolnei; da Silva Torres, Iraci Lucena (Clinical and Biomedical Research, 2017)
Introduction: The transcranial direct current stimulation (tDCS) is a non-invasive technique, which induces neuroplastic changes in the central nervous system of animals and humans. Furthermore, tDCS has been suggested as a therapeutic tool for pain management. The aim of this study was to standardize a non-invasive tDCS technique indexed by the nociceptive response of rats submitted to different conditions necessary to the tDCS application. Method: 60-day-old male Wistar rats (n=65), divided into 6 groups: control(C); non-active sham (NAS); active-sham (AS); active-sham restrained (ASR); non-active sham restrained (NASR); active tDCS treatment. Animals received treatment during 30 seconds (sham-active) or 20 minutes (restraint and tDCS)/8 days. Nociceptive threshold was assessed by Hot Plate test at baseline, immediately and 24h after the first session, immediately and 24h after the last session. Variance analysis of repeated measurements followed by Bonferroni was performed for intra-group comparison. Results: Physical restraint and 30 seconds stimulation (sham-tDCS) increased pain sensitivity (P≤0.05), and tDCS treatment was able to prevent the thermal hyperalgesia. Our original tDCS montage is similar to that used in the procedure with humans, because it is not an invasive technique. The electrodes are positioned on the head, and the animals are immobilized during the 20-minute treatment. As this procedure could involve behavior and neurochemical alterations due to stress induced by restriction (thus, it creates a research bias), we hypothesized that a 30-second electrical stimulus application (sham-tDCS) and the physical restriction used during tDCS treatment might alter nociceptive response in rats. Conclusion: There are methodological limitations in the present tDCS-technique. Although active-tDCS treatment is able to prevent these harmful effects, interference of these factors has to be considered during the results’ analysis. Future adaptations of the tDCS-technique in rats are required to evaluate its therapeutic effects. Keywords: tDCS; animal model; nociception; thermal hyperalgesia; stress restraint